Enhancing wine fermentation through concurrent utilization of Lachancea thermotolerans and lactic acid bacteria (Oenococcus oeni and Lactiplantibacillus plantarum) or Schizosaccharomyces pombe - Javier Vicente; Li Wang; Silvia Brezina; Stefanie Fritsch; Eva Navascués; Antonio Santos; Fernando Calderón; Wendu Tesfaye; Domingo Marquina; Doris Rauhut; Santiago Benito (Food Chemistry: X)
Most commercially available red wines undergo alcoholic fermentation by Saccharomyces yeasts, followed by a second fermentation with the lactic acid bacteria Oenococcus oeni once the initial process is complete. However, this traditional approach can encounter complications in specific scenarios. These situations pose risks such as stalled alcoholic fermentation or the growth of undesirable bacteria while the process remains incomplete, leaving residual sugars in the wine. To address these challenges and the issue of low acidity prevalent in warmer viticultural regions, several novel alternatives are available. The alternatives involve the combined use of Lachancea thermotolerans to increase the acidity of the musts, lactic acid bacteria (Oenococcus oeni and Lactiplantibacillus plantarum) to ensure malic acid stability during early alcoholic fermentation stages, and Saccharomyces cerevisiae to properly complete alcoholic fermentation. The study showed variations in the final chemical parameters of wines based on the microorganisms used.